Dopamine (D1) Receptors and Single Nucleotide Polimorphisms (SNPs) in Patients with Cognitive Impairment of Major Depressive Disorder (MDD). - Sahar Mohamed Kamal Shams El Dine (Open Journal of Proteomics and Genomics - Peertechz Publications, 2017)
A gene is the basic component of each chromosome in any cell of human body. It controls the heredity in human being and all other species. Adenine, Guanine, Thymidine and Cytosine (A, G, T, and C) are the bases of nucleotides that are ordered in a well-designed and in a proper sequence on the surface of each chromosome in the form of genes together with sugar and phosphate.